Stigmatic aspects of cancer theme in the Turkish cinema and television sector - Doğan, Sibel; Ceylan, Can (Wiley-Blackwell, 2015)
BACKGROUND/PURPOSE: Stigmatization—to brandsomebody with some mark of reproach or infamy—isthe whole of the actions taken by the society againstsome patient groups—as much as to isolate them.
WOS: 000358255000624
Keywords: Stigmatic; Cancer; Television Sector